Epidemiological evaluation paediatric burn injuries via an outpatient database in Eastern Ontario - Katie Garland; Nima Nahiddi; Brent Trull; Claudia Malic (Elsevier, 2018)
Background: Burn injuries account for significant morbidity in the pediatric population. There is no structured data to describe the pediatric burns epidemiological profile in Eastern Ontario, Canada. Objectives: The aim was to establish a pediatric burn database in order to assess our current standard of practice, the burn epidemiology, and develop a framework for focused burn prevention programs in our catchment area. Methods: A pediatric burn database was built in REDCap at the Children's Hospital of Eastern Ontario (CHEO) retrospectively for 2010-2015 period. Data points included demographic data, details about the injury and description of the burn wounds. Rural and urban living was classified as per the Canadian Postal Service. Results: A total of 695 patients were seen as outpatients. Burns included 51.6% scald, 30.6% contact, and 9.6% flame injuries. Mean age was 4.25 years, and mean burn extent was 4.4% total body surface area (TBSA). Patients from rural areas had sustained burns wounds due to flame and contact with hot surfaces (p < 0.05), whereas children from urban areas had hot liquids as main etiology (p < 0.05). Conclusion: The pediatric burn injuries in our catchment area are mainly scald burns, and relatively small. The newly created outpatients burn database will aim to tailor the burn prevention programs. Primary burn prevention through education is essential in future burn reduction strategies. Keywords: Burns, Scald, Flame, Rural, Urban, Retrospective review, Database